RESPON TANAMAN BAWANG MERAH (Allium ascalonicum L.) VARIETAS LEMBAH PALU TERHADAP PEMBERIAN JENIS MULSA DAN PUPUK ORGANIK CAIR - As?ad surajudin. L, RamalYusuf, HidayatiMas?ud, As?ad (AGROTEKBIS, 2015)
The research was conducted at Bulu Pounto Jaya, Biromaru sub District, Sigi District, Central Sulawesi Province from August to November 2014. This research aimed to determine the effect of mulch and liquid organic fertilizer types on growth and yield of shallot (Allium ascalonicum L.) Lembah Palu varieties. The design used in this research was a two factorial randomized block design (RAK). The first factor was application of mulch (M) i.e. M0 = no mulching, M1 = silver black plastic mulching, M2 = rice straw mulch and the second factor was the application of liquid organic fertilizer i.e. F1 = once application (7 days after planting-WAP), F2 = twice applications (7, 14 DAP), F3 = thrice applications (7, 14, 21 DAP). Therefore, there were nine combinations of treatments and replicated three times. The results showed that the type of mulch (M) affected significantly the components of plant height, number of leaves, leaf area, plant fresh weight, and tuber fresh weight. The liquid organic fertilizer treatment (F) had a significant effect on the components of leaf area and plant fresh weight. The rice straw mulch (M2) produced higher growth than the silver black plastic mulch (M1) and without mulch (M0). While the liquid organic fertilizer applied three times (F3) produced higher yield than the other applications. There was significant interaction effect between the two factors on leaf area components.